A new algorithm to identify nonlinear vibration of car body in white (BIW) structure - Sani, M. S.M.; Ghazali, M. F.; Baharom, Mohamad Zairi; Yusof, Mohd Fadhlan M.; Rahman, M. M. (2013)
In this project, the nonlinear force appropriation identification approach is applied to the detection of nonlinear or piecewise linear stiffness. The methodology will demonstrate using both simulations and experiments by hanging the car body structure with proper elastics bungee cord. The finite element models of the body structures will built in finite element package and perform model updating to minimise error between experimental and numerical results. Mass and stiffness matrices can be extracted after model updating process. The force appropriation method is implemented to determine the force vector that would excite a single mode of the underlying linear structure a time. At the end of the research, the propose method is expected to identify nonlinearity of car body structure.